2017
DOI: 10.1111/cen.13517
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Müllerian hormone measurement for the diagnosis of polycystic ovary syndrome

Abstract: Whilst an elevated AMH has poor sensitivity, it is fourfold more likely to be associated with a diagnosis of PCOS, and supplementary to biochemical parameters will make a positive diagnosis of PCOS in 22% of patients when neither serum testosterone nor FAI is elevated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 17 publications
8
31
0
Order By: Relevance
“…This value is more stringent than the AMH threshold value (33.5 pmol/L or 4.7 ng/mL) determined by meta‐analysis of the extracted data from studies published prior to 2013 . In line with observations from another study, AMH alone, demonstrated poor sensitivity diagnosing about 34% more women as having PCOS compared to Rotterdam 2003. These data are in line with finding observations made by PCOS cases identified by AMH alone had significantly lower prevalence of oligomenorrhoea, lower androgen and metabolic indices, arguing against the adoption of AMH as a single biomarker for PCOS.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This value is more stringent than the AMH threshold value (33.5 pmol/L or 4.7 ng/mL) determined by meta‐analysis of the extracted data from studies published prior to 2013 . In line with observations from another study, AMH alone, demonstrated poor sensitivity diagnosing about 34% more women as having PCOS compared to Rotterdam 2003. These data are in line with finding observations made by PCOS cases identified by AMH alone had significantly lower prevalence of oligomenorrhoea, lower androgen and metabolic indices, arguing against the adoption of AMH as a single biomarker for PCOS.…”
Section: Discussionsupporting
confidence: 58%
“…This value is more stringent than the AMH threshold value (33.5 pmol/L or 4.7 ng/mL) determined by meta-analysis of the extracted data from studies published prior to 2013 19. In line with observations from another study,34 AMH alone, demonstrated poor sensitivity diagnosing about 34% more women as having PCOS compared to…”
supporting
confidence: 58%
“…AMH is produced in the granulosa cells by the preantral and small antral follicles and it appears to inhibit the action of FSH on aromatase, and therefore, it contributes to the development of a single follicle for ovulation. 8 It has also been suggested that serum AMH reflects ovarian size in PCOS patients and can be used as surrogate for transvaginal ultrasound in the diagnosis of PCOS. 22 We have recently shown that those with raised AMH have up to 4fold increased risk of having PCOS.…”
Section: P-value * Median (Iqr) Median (Iqr)mentioning
confidence: 99%
“…The study and study measurements are described in detail in our previous publication. 8 In summary, we measured body mass index (BMI) (kg/m 2 ), waist circumference (cm), hip circumference (cm), AMH (pmol/L), salivary testosterone (pmol/L), total testosterone (nmol/L), salivary androstenedione (pmol/L), serum androstenedione (nmol/L), SHBG (nmol/L), FAI (%), follicle-stimulating hormone (FSH) (IU/L), luteinizing hormone (LH) (IU/L), fasting glucose (mmol/L), 2-hour glucose (mmol/L), insulin (μIU/mL) according to established protocols in women with PCOS and controls. We also ascertained oral contraceptive use and history of menstrual irregularity/amenorrhoea.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation